ANALISIS LAPORAN KEUANGAN USAHA MIKRO KECIL MENENGAH (UMKM) PRODUK FASHION HIJAB DENGAN MENGGUNAKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) - Nurul Khotimah, Siti; Wiranti, Ayu; Wahyuningsih, Wahyuningsih; Salsabila, Amelia; Prasetyo, Adhy; Yulfajar, Amrina (Widya Warta, 2021)
The Covid-19 pandemic has brought the national economy to a global recession. One of the business sectors affected by the Covid-19 pandemic is MSMEs which are also the reason for the decline in economic conditions in Indonesia. MSME is a business sector that has economic contribution to Indonesia's GDP by 61.1%. However, many business actors are unaware of the importance of recording each financial transaction of its business to see and analyze their business developments regularly. This study aimed to analyze the financial statements of Latusha Hijab MSME by taking into account the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). The object of this research was Latusha Hijab, a new MSME in the field of hijab fashion. The data collection used observation and interview methods. The results showed that the recording of financial reports by Latusha Hijab was not in accordance with the principles of the SAK EMKM. Therefore, further assistance was necessary to provide additional knowledge and skills regarding how to record financial reports correctly and properly.